Allocative Efficiency of Markets with Zero-Intelligence Traders: Market as a Partial Substitute for Individual Rationality - Gode, Dhananjay K.; Sunder, Shyam (Journal of Political Economy, 1993)
This paper reports market experiments in which human traders are replaced by "zero-intelligence" programs that submit random bids and offers. Imposing a budget constraint (i.e., n ot permitting traders to sell below their costs or buy above their valu es) is sufficient to raise the allocative efficiency of these auctions close to 100 percent. Allocative efficiency of a double auction deri ves largely from its structure, independent of traders' motivation, intelligence, or learning. Adam Smith's invisible hand may be more powerful than some may have thought; it can generate aggregate rationality not only from individual rationality but also from individual irrationality. Copyright 1993 by University of Chicago Press.